Sustainable marketing : a holistic approach - Peterson, Mark (Thousand Oaks, California : SAGE, 2021)
"This unique book explores the sustainability practices that benefit companies, stakeholders and society, by drawing upon the latest research and industry examples. Dissecting the interplay between marketing and society, Peterson encourages us to critically assess the demand for businesses to engage with sustainability guidelines and environmental concerns while remaining profitable"--
Includes bibliographical references and index.
Keywords: Marketing. Distribution of products; Green marketing